The long road to closed cycle management: So far, environmental protection in the capital equipment producing industry has aimed primarily to reduce the production-related emissions - Carsten Dreher; Elna Schirrmeister (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2000)
In the 1990s, recession and high unemployment meant that environmental protection was no longer a domain of action in the foreground of discussion, although the urgency of making industrial activities sustainable remains as great as ever. For this very reason, the Fraunhofer ISI has been analysing the environmental protection activities of the capital equipment producing industry. Results of the analysis indicate that the managers questioned in the survey attribute great importance to closed cycle management approaches. This positive attitude is not yet reflected, however, in terms of concrete management. Thus only about one firm in seven offers its customers the facility of taking back used products. Management concepts that support closed cycle management, such as Life Cycle Costing or ecological audits, are even less widespread. Nevertheless, an examination of firms' aims indicates that these concepts will become increasingly important within the next few years. Traditional investments in equipment for reducing environmental pollution of clean air, clean water an clean earth continue to be the most frequently named measures. The average performance indicators of firms actively engaged in environmental protection are well up to, and in some cases better than, the average for firms as a whole.
Keywords: 330